Evaluation of Magnetic Stirring and Aeration on Electrocoagulation Performance in Actual Industrial Treatment - Trinh, Dang Trung Tri; Binh, Quach An; Ty, Tran Van; Channei, Duangdao; Nakaruk, Auppatham; Khanitchaidecha, Wilawan (Frontiers in Environmental Science, 2021)
The agitation was a significant factor for achieving the high performance of electrocoagulation (EC) system. The different agitations of stirring and aeration were implied to the hybrid EC system with the aim of maximizing the industrial wastewater treatment in a short electrolytic time. The coolant wastewater from an aluminum product industry was represented as industrial wastewater in this work. The hybrid stirring-aeration EC system obtained a lower COD removal rather than the stirring EC system and the aeration EC system. Although the aeration can cause the increasing COD removal due to complete circulation and effective coagulant of Fe(OH)3 formation, however the combination of aeration and stirring negatively affected the EC performance. The possible reason was that the excessive agitation led to a rapid mixing of the solution, then the coagulants and pollutants obtained insufficient time to form as flocs to precipitate. The best EC performance was observed in the aeration EC system, and followed by stirring EC system, control system (without agitations) and the stirring-aeration EC system respectively in the short electrolytic time of 15 min. In addition, all EC systems could reach the excellent COD removal of 90% when the electrolytic time was sufficient (e.g., 45 min for the stirring-aeration EC system). Furthermore, the decreasing number of electrodes was affected on the COD removal efficiency, whereas the NaCl additive was insignificantly effected.